PROFILE OF STUDENTS’ PROBLEM SOLVING ABILITY WITH INTEGRATED SCIENCE MODEL BASED ON DISASTER MITIGATION - Febrianto, Erwin; Hidayati, Yunin; Puspitahadi, Wiwin (Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
This study aimed to determine students' problem-solving abilities with an integrated science model based on disaster mitigation. This study used a quasi-experimental method with a nonequivalent control group design. This research was conducted at Benjeng 1 Public Middle School with a population of all students in grade VII and samples in grades VII F and VII G. Data collection using a problem-solving ability test with Polya indicators. Data analysis using the free sample t-test through the SPSS version 20. Based on the results of the study it can be concluded that there is a difference in the problem solving ability between the experimental class and the control class, obtained the results of the free sample t-test with a significance of 0.028 and the test criteria –t-count <t-table <t-count of -2,252 <2,000 <2,252.